If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 3) = 12 + -1y Reorder the terms: 7(3 + x) = 12 + -1y (3 * 7 + x * 7) = 12 + -1y (21 + 7x) = 12 + -1y Solving 21 + 7x = 12 + -1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 7x = 12 + -21 + -1y Combine like terms: 21 + -21 = 0 0 + 7x = 12 + -21 + -1y 7x = 12 + -21 + -1y Combine like terms: 12 + -21 = -9 7x = -9 + -1y Divide each side by '7'. x = -1.285714286 + -0.1428571429y Simplifying x = -1.285714286 + -0.1428571429y
| x^2-2x-220=0 | | (4a-4)=8a-(4a-16) | | 4g+2(-3+3g)=1-g | | p+.02p=183.6 | | (5x+8)=(10x-2) | | 4x=9(x+4) | | 8+x=20+5x | | 6x+6=3x+4 | | -4(-5h-4)=2(10+8) | | 0=-3x^2-2x-15 | | 2*x^4-3*x^3-3*x^2+10*x+10=0 | | y=-3x^2-12x-3 | | 24b=8 | | w*2-23*w+42=0 | | y-10=0(x+7) | | -3(h-6)=5(x+4)-2x | | 500x-2325=3950 | | 5-3*(4-6)= | | -2(7x-3)=76 | | 10x^2-39x+23=30 | | 15+x=-28 | | 4(y-2)-2=-3(-6y+2)-6y | | 10x^3-39x^2-23x+30=0 | | 3x^2+14=x^2+29 | | 2x+4+(-4x+9)= | | 7x^2+1y=9 | | 6x-11+2x=5+8x-16 | | -2(y+3)=y-9+3(4y+7) | | 0.08x=7.50+0.05 | | 1.03x+2.1=3.13 | | 2x+37=83 | | 14.3x=12.9 |